What do people appreciate in physicians' communication? An international study with focus groups using videotaped medical consultations. (25th June 2013) - Mazzi, Maria A.; Rimondini, Michela; Deveugele, Myriam; Zimmermann, Christa; Moretti, Francesca; van Vliet, Liesbeth; Deledda, Giuseppe; Fletcher, Ian; Bensing, Jozien
Abstract: Background: The literature shows that the quality of communication is usually determined from a professional perspective. Patients or lay people are seldom involved in the development of quality indicators or communication. Objective: To give voice to the lay people perspective on what constitutes 'good communication' by evoking their reactions to variations in physician communication. Design: Lay people from four different countries watched the same videotaped standardized medical encounters and discussed their preferences in gender‐specific focus groups who were balanced in age groups. Setting and participants: Two hundred and fifty‐nine lay people (64 NL, 72 IT, 75 UK and 48 BE) distributed over 35 focus groups of 6–8 persons each. Main variables studied: Comments on doctors' behaviours were classified by the GULiVer framework in terms of contents and preferences. Results: Participants prevalently discussed 'task‐oriented expressions' (39%: competency, self‐confident, providing solutions), 'affective oriented/emotional expressions' (25%: empathy, listening, reassuring) and 'process‐oriented expressions' (23%: flexibility, summarizing, verifying). 'Showing an affective attitude' was most appreciated (positive percentage within category: 93%, particularly facilitations and inviting attitude), followed by 'providing solution' (85%). Among disfavoured behaviour, repetitions (88%), 'writing and reading' (54%) and asking permission (42%) were found. Conclusions: Although an affective attitude is appreciated by nearly everybody, people may vary widely in their communication needs and preferences: what is 'good communication' for one person may be disliked or even a source of irritation for another. A physician should be flexible and capable of adapting the consultation to the different needs of different patients. This challenges the idea of general communication guidelines.